Congenital Lobar Overinflation: A Rare Enigmatic Lung Lesion on Prenatal Ultrasound and Magnetic Resonance Imaging. (12th September 2018) - Oliver, Edward R.; DeBari, Suzanne E.; Horii, Steven C.; Pogoriler, Jennifer E.; Victoria, Teresa; Khalek, Nahla; Howell, Lori J.; Adzick, N. Scott; Coleman, Beverly G.
Abstract : Objectives: To report the ultrasound (US) features in prenatal cases of suspected congenital pulmonary airway malformation or unspecified lung lesions with a final surgical pathologic diagnosis of congenital lobar overinflation (CLO). Methods: Institutional Review Board–approved radiology and clinical database searches from 2001 to 2017 were performed for prenatally diagnosed lung lesions with a final diagnosis of CLO. All patients had detailed US examinations in addition to magnetic resonance imaging (MRI). Size, echotexture, and vascularity were assessed with US, and the signal and vascularity were assessed with MRI. Follow‐up prenatal US scans, postnatal imaging, and postnatal outcomes were reviewed. Results: The study population consisted of 12 patients. The median gestational age was 23.3 weeks. The median congenital pulmonary airway malformation volume‐to‐head circumference ratio was 0.66. Lesion locations were 6 in the lower lobes (4 right and 2 left), 5 in the upper lobes (3 left and 2 right), and 1 in the right middle lobe. The texture was homogeneously echogenic relative to the normal lung in 100% with no visualized macrocysts. Hypervascularity by color Doppler US was observed in 5 cases (41.7%). A T2 hyperintense lung lesion was identified by MRI in 12 of 12 cases (100%), with elongated vessels identified in 11 of 12 cases (91.7%). All 12 cases had pathologically proven CLO. Conclusions: Congenital lobar overinflation should be considered in cases of prenatal echogenic lung lesions without macrocysts or classic findings of bronchial atresia. Hypervascularity may be an important imaging feature of a subset of CLO. Most cases become less conspicuous, decrease in size without overt hydrops, and are asymptomatic postnatally.